2022
DOI: 10.1002/pbc.30110
|View full text |Cite
|
Sign up to set email alerts
|

The tumor microenvironment and immune targeting therapy in pediatric renal tumors

Abstract: This review highlights the role of several immunomodulating elements contributing to the tumor microenvironment of various pediatric renal tumors including Wilms tumor.The roles of innate and adaptive immune cells in renal tumors are summarized as well as immunomodulatory cytokines and other proteins. The expression and the predictive role of checkpoint modulators like PD-L1 and immunomodulating proteins like glypican-3, B7-H3, COX-2 are highlighted with a translational view toward potential therapeutic innova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 173 publications
0
2
0
Order By: Relevance
“…Surgical resection is the ideal method for treatment of KIRC patients, unfortunately a great number of patients are suffered from tumor recurrence after surgery ( 30 , 31 ). Currently, immunotherapy is an emerging direction for KIRC treatment ( 32 , 33 ). Therefore, finding new biomarkers associated with the immunomodulation is of significance for KIRC precision and personalized medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection is the ideal method for treatment of KIRC patients, unfortunately a great number of patients are suffered from tumor recurrence after surgery ( 30 , 31 ). Currently, immunotherapy is an emerging direction for KIRC treatment ( 32 , 33 ). Therefore, finding new biomarkers associated with the immunomodulation is of significance for KIRC precision and personalized medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Data from the literature suggest that Wilms tumor is an immune-engaged tumor. An immune infiltrate analysis showed that CD8 and CD4 T cells were localized in a tumor and exhibited an activated phenotype [ 112 ], with the presence of activated CD8 T cells correlating with positive outcomes [ 113 ]. However, the TME may include immunosuppressive cells such as Tregs and increased plasmacytoid DCs.…”
Section: Tme Immune Profiling In Pediatric Solid Tumorsmentioning
confidence: 99%
“…Immune profiling of pediatric brain tumor patient-derived orthotopic xenografts (PDOX), representing both low and high grades, consistently demonstrated the presence of B7-H3 and GD2 on tumor cell surfaces [ 66 ]. Similarly, B7-H3 has been found to be associated with poor anti-tumor immunity, therapy response, and prognosis in other pediatric tumor types such as AML, medulloblastoma, Wilms tumor, and rhabdomyosarcoma [ 67 , 68 , 69 , 70 ]. This suggests that B7-H3 may be involved in regulating the immune response within the pediatric brain tumor microenvironment.…”
Section: Influence Of the Immune Microenvironment On Pediatric Tumor ...mentioning
confidence: 99%